The vacuolar pathway of long peptide cross-presentation can be TAP dependent - Ma, W; Stroobant, V; Heirman, C; Sun, Z; Thielemans, K; Mulder, A; Van Der Bruggen, P; Van Den Eynde, B (American Association of Immunologists, 2019)
The intracellular pathway of cross-presentation, which allows MHC class I–restricted presentation of peptides derived from exogenous Ags, remains poorly defined and may vary with the nature of the exogenous Ag and the type of APC. It can be cytosolic, characterized by proteasome and TAP dependency, or vacuolar, usually believed to be proteasome and TAP independent. Cross-presentation is particularly effective with long synthetic peptides, and we previously reported that the HLA-A2–restricted cross-presentation of a long peptide derived from melanoma Ag gp100 by human monocyte-derived immature dendritic cells occurred in a vacuolar pathway, making use of newly synthesized HLA-A2 molecules that follow a nonclassical secretion route. In this article, we show that the HLA-A1–restricted cross-presentation of a long peptide derived from tumor Ag MAGE-A3 by human monocyte-derived immature dendritic cells also follows a vacuolar pathway. However, as opposed to the HLA-A2–restricted peptide, cross-presentation of the HLA-A1–restricted peptide is TAP dependent. We show that this paradoxical TAP-dependency is indirect and reflects the need for TAP to load HLA-A1 molecules with peptides in the endoplasmic reticulum, to allow them to escape the endoplasmic reticulum and reach the vacuole, where peptide exchange with the cross-presented peptide likely occurs. Our results confirm and extend the involvement of the vacuolar pathway in the cross-presentation of long peptides, and indicate that TAP-dependency can no longer be used as a key criterion to distinguish the cytosolic from the vacuolar pathway of cross-presentation. They also stress the existence of an alternative secretory route for MHC class I, which will be worthy of further studies.